The strength of social capital of three local communities at Gunung Pueh National Park, Lundu, Sarawak - Hasan, Muhammad Luqman; Thoo, Poh Yee; Yee, Lai Ling; Johari, Shazali; Emang, Diana (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Social capital is an important concept in identifying the connection and relationship of the community, which has three dimensions: bonding, bridging and linking social capital. Since nowadays the issues related to trust, criminal and relationship has been a serious problem in our community, hence the measurement to determine the strength of social capital dimension has been conducted. The initial process has been explored to identify the suitable social capital indicators. The result is then used to construct into an instrument comprising six indicators based on survey items and past studies namely participation in local community, proactive in social context, neighborhood connection, diversity and tolerance, feeling trust and safety and family and friends connection. This is a quantitative study involving 390 respondents with the self-administered questionnaire distributed in three communities at Gunung Pueh National Park which are Kampung Biawak, Kampung Sebako and Kampung Pueh. The result revealed that bonding social capital is strongly hold the communities followed by linking and bridging social capital. At the other hand, the result showed Kampung Pueh has the strongest overall social capital followed by Kampung Sebako and Kampung Biawak.